PENGARUH PENERAPAN MODEL EXAMPLES NON EXAMPLES PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA DI KELAS X IIS SMA MUHAMMADIYAH I PONTIANAK - Sonia, Sonia; Sulistyarini, Sulistyarini; Christan, L.M Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThias reseach aimed to analyze about how high was the affect of the implemented of the model of examples non examples in geogrhy subject on the material of the dynamics of hydrosfer and the impact used for life toward the student achievement on grade ten of IIS of SMA muhammadiyah I Pontianak the method used in this researchwas quasy experiment with non equvakent control group design. The population of this research was all of ten grade IIS of SMA Muhammadiyah I Pontianak which consist of 135 students. The technique sampling chose were probality sampling. The tools of collecting theÂ data were a test of students achievement with objective questions. In experiment class the result showed r ratio was (3.50840) and t critical with a = 5% and dk =63 was (1,411), it meant that Ha of examples non examples in geography subject on the material of the dynsmics of hydrosfer towards the student achievement on grade ten of IIS of SMA MuhammadiyahÂ I Pontianak . Based on the data of effect size, the data showed that ES was 0,90 the model of examples non examples in geograpy subject has given the high affect towerds the students achievement on grade ten of IIS of SMA Muhammadiyah I Pontianak.Â Keywords: The affect, the model examples non examples, student achievement.